The Implementation of Framework for Edutainment: Educational Games Customization Tool - Che Embi, Zarina (2008)
Computer games have been identified as the potential tool in education especially when it involves the children. Although there are plenty of computer games which are claimed as educational, it is a difficult task to select one that can fulfil the requirements. In this paper, the framework for edutainment that may be implemented in a game-based learning environment will be discussed. It will further report on the implementation of the framework through the development of a prototype of a tool to customize an educational game, using an evolutionary prototyping method The prototype was developed as a final year project by a group of undergraduates of the Faculty of Information Technology, Multimedia University, Malaysia. In view of the current growth of the use of games in learning, the need for such tools will become more predominate. How such games are designed will surely influence their effectiveness in enhancing learning.